A Framework for Assessing Technology-Mediated IPV. Issue 4 (1st October 2020) - Hertlein, Katherine M.; Eddy, Brandon P.; Lancaster Strickland, Morgan
Abstract: Intimate partner violence (IPV) is a common public health problem that damages many romantic relationships. It is defined as abuse or aggression that occurs between intimate partners with an estimated ⅓ of women worldwide having some experience as the recipient of IPV at some point in their lives. While couple therapists are improving their ability to recognize the presence of IPV in practice, there are still gaps in assessment, especially as it pertains to the role technology plays in facilitating and exacerbating IPV. Given the dangers and damage resulting from IPV, it is imperative for couple therapists to assess broadly and across many contexts for the prevalence of technology-mediated IPV. The purpose of this article is to inform clinical practice by (1) presenting reasons why couple therapists overlook technology-mediated violence, and (2) present strategies for therapists to better address technology-mediated IPV.